Fungal Infections Complicating COVID-19 - Hoenigl, Martin; Talento, Alida Fe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), spread globally to pandemic proportions. Although the majority of cases have asymptomatic or mild infections, a significant proportion of cases progress to severe pneumonia and acute respiratory distress syndrome requiring critical care. Opportunistic infections following severe respiratory viral infections have been recognized since the 1918 influenza pandemic. Among critically ill patients with COVID-19, secondary fungal infections caused by Aspergillus and Candida spp. are increasingly described, affecting up to 30% of COVID-19 patients requiring intensive care treatment. This collection of manuscripts focuses on fungal infections complicating COVID-19, including immunological mechanisms and pathogenesis, diagnosis, and treatment.